EFFECT OF WORKING CAPITAL, LIQUIDITY ON FINANCIAL PERFORMANCE WITH POLITICAL CONNECTION MODERATION - Mardhufa, Hilda Alicia; Alamsyah, Sustari; Zatira, Dhea (Jurnal Riset Terapan Akuntansi, 2025)
Several companies listed on the Kompas100 Index face challenges in maintaining their profitability levels. Empirical data reveals that several companies included in the Kompas100 Index experienced fluctuations. This study aims to examine how Working Capital and Liquidity affect the financial performance of companies listed on the Indonesia Stock Exchange Kompas100 Index during the 2019-2023 period, as well as the moderating role of Political Connections. The research sample consisted of 32 companies from 53 populations selected through purposive sampling techniques, secondary data used came from the company's financial statements and were analyzed using the panel data regression method. The results show that working capital and political connections affect financial performance positively and significantly, while liquidity does not affect it significantly. Political connections do not moderate the relationship between working capital and financial performance, but negatively moderate the relationship between liquidity and financial performance. These findings suggest that efficient working capital management and political connections can enhance financial performance, but political ties may weaken the impact of liquidity, requiring firms to carefully consider the role of political connections in their financial strategies. Keywords: Financial Performance, Working Capital, Liquidity, Political Connection.